Optimization of the laboratory diagnosis of allergies with regard to regional peculiarities - V.А. Кlymenko; J.V. Кarpushenko; А.V. Servetnik (Zaslavsky O.Yu., 2015)
Allergic pathology is one of the most pressing issues in contemporary medicine. The most important task during the treatment of allergic diseases is the determination of cause-significant allergens. Nowadays, the identification of specific IgE in the blood serum is widely used in Ukraine for the diagnostics of food and respiratory allergies. The majority of the laboratories offer the identification of specific IgE in the form of panels, the composition of which not exactly corresponds to our regional peculiarities. This article presents the results of the analysis of 790 medical histories of children aged 3-17 years with allergic pathology. Sensitization to allergens has been identified by determining the specific IgE in the blood serum and by skin prick testing. As a result, the following relevant food allergens were detected: fish, beans, strawberry, wild strawberry, apricot, peach, raspberry, cherry, sweet cherry, plum, apple, pear, citrus fruits, chicken protein, cow's milk protein. Representative pollen allergens of Kharkiv region are: ragweed, sagebrush, sumpweed, dandelion, buckwheat, sorrel, poplar, acacia, maple, alder, oak. To optimize laboratory diagnostics in the Kharkiv region when preparing test panels, it is recommended to separately identify food and pollen allergens based on their relevance. The composition of the panels of pollen allergens should be reviewed, taking into account the data of the regional aeropalynologic researches.